The 9p21 Rs 1333040 polymorphism is associated with coronary microvascular obstruction in ST-segment elevation myocardial infarction treated by primary angioplasty. Issue 8 (1st December 2019) - Fracassi, Francesco; Niccoli, Giampaolo; Vetrugno, Vincenzo; Cauteruccio, Michele; Buffon, Antonino; Gatto, Ilaria; Giarretta, Igor; Tondi, Paolo; Pola, Roberto; Crea, Filippo
Abstract: Background: Microvascular obstruction (MVO) after primary percutaneous coronary intervention (pPCI) leads to higher incidence of both early and late complications. A number of single nucleotide polymorphisms in 9p21 chromosome have been shown to affect angiogenesis in response to ischaemia. In particular, Rs1333040 with its three genotypic vriants C/C, T/C and T/T might influence the occurrence of MVO after pPCI. Methods: We enrolled ST-elevation myocardial infarction (STEMI) patients undergoing pPCI. The Rs1333040 polymorphism was evaluated by polymerase chain reaction-restriction fragment length polymorphism using restriction endonucleases (Bsml). Two expert operators unaware of the patients' identity performed the angiographic analysis; collaterals were assessed applying Rentrop's classification. Angiographic MVO was defined as a post-pPCI Thrombolysis In Myocardial Infarction (TIMI)<3 or TIMI 3 with myocardial blush grade 0 or 1, whereas electrocardiographic MVO was defined as ST segment resolution <70% one hour after pPCI. Results: Among our 133 STEMI patients (mean age 63 ± 11 years, men 72%), 35 (26%) and 53 (40%) respectively experienced angiographic or electrocardiographic MVO. Angiographic and electrocardiographic MVO were different among the three variants ( p = 0.03 and p =0.02 respectively). In particular, T/T genotype was associated with a higher incidence of both angiographic and electrocardiographic MVO compared with C/C genotype ( p =0.04 and p =0.03 respectively). Moreover, Rentrop score <2 detection rate differed among the three genotypes ( p =0.03). In particular T/T genotype was associated with a higher incidence of a Rentrop score <2 as compared with C/C genotype ( p = 0.02). Conclusion: Rs1333040 polymorphism genetic variants portend different MVO incidence. In particular, T/T genotype is related to angiographic and electrocardiographic MVO and to worse collaterals towards the culprit artery.